Ensaios sobre economia da educação no Ceará – avaliação dos Subprogramas jovem de futuro (PJF), o programa professor diretor de turma (PPDT) e efeito distância casa-escola - Sousa, Cinthia Barbosa (2023)
This thesis includes three articles that present theoretical and empirical foundations in order to investigate and understand the determinants of academic proficiency of students from Ceará. The first chapter analytically addresses the effect of a set of methodologies (or sub-programs) of the Programa Jovem de Futuro (PJF) on academic performance. These methodologies consist of adapted pedagogical and/or articulation and mobilization activities, formulated to meet the program's stipulated goals and which were adopted at different levels in public schools in Ceará. The program contemplated one of the few social experiments in education in Brazil, and the differentiated adoption among schools allowed investigating impacts in three levels of treatment in Portuguese Language and Mathematics (SPAECE) scores, using the technique of Propensity Score for Multiple Treatments, ponderada por Generalized Boosted Models (GBM) de McCaffreya et al. (2013). The results showed that a combination of mixed methodologies (essential and optional) showed greater positive effects than the most basic combinations, and that this effect was greater in the Portuguese language grade compared to the math grade. The second chapter also investigates the impacts on proficiency of the Teacher Director of the Class Program (PPDT) in which it aims to promote integration between students, teachers and parents through a class manager who can provide individualized attention to students, seeking to know them better, have information about your life history, interests, attitudes and future prospects. The program's guidelines point to the use of effective teachers with exclusive dedication to the school for the role of class director. However, not all schools adopt this guideline, which generates two types of treatments: i) standard (which follows the guidelines), and ii) non-standard (which does not follow the guidelines). This differentiation into levels also makes it possible to investigate impacts through the modeling of Propensity Score for Multiple Treatments de McCaffreya et al. (2013). The results pointed to a differentiated effect of the program on Mathematics and Portuguese grades, suggesting positive and significant effects in the first subject, and even greater for those who followed the guidelines, and null or even negative effects for the second subject. Finally, the third chapter aims to empirically investigate the effect of distance from households to schools located in municipalities in the metropolitan region of Fortaleza (Fortaleza, Caucaia, Maracanaú and Eusébio). The article is unique in the construction of an unprecedented database that crossed micro economic, social, and georeferenced information on CadÚnico families for the year 2018 with the performances of SPAECE for the same year. Using multilevel linear regression methodology, the results suggest that when controlling for the qualifying characteristics of the schools, the distance effect is no longer significant.